Balance this reaction if necessary: ca3(po4)2+h2so4–> caso4+h3po4 a)balanced b)1,3,3,2 c)1,2,3,3 d)3,2,1,3

Choice B. 1,3,3,2 Explanation: Ca3(PO4)2 + 3H2SO4 –> 3CaSO4 + 2H3PO4

Choice (b) may be the proper solution. Explanation: once we state that an equation is balanced it suggests you can find equal few atoms on both reactant and item part. Like, few atoms on reactant part tend to be below. Ca = 3 = 2H = 2 = 1 few atoms on item part tend to be below. Ca = 1 = 1H = 3 = 1 consequently, to stabilize this equation we multiply by 3 on reactant part and boost by 3 and by 2 on item part. Thus, the balanced equation is below.

Ca3(PO4)2 + 3H2SO4 → 3CaSO4 + 2H3PO4

Answer 6

Ca3(PO4)2 + 3H2SO4 → 3CaSO4 + 2H3PO4 Hope this answers issue. Have actually an excellent time.

Leave a Comment